A new bat species of the genus Myotis with comments on the phylogenetic placement of M. keaysi and M. pilosatibialis - Carrion-Bonilla, Carlos Alberto; Cook, Joseph Anthony (THERYA, 2020)
Molecular studies of Neotropical Myotis (Chiroptera, Vespertilionidae) in the last decade have uncovered substantial cryptic diversity. One example is M. keaysi pilosatibialis, which is characterized by a complex taxonomy derived from low morphological variation. Herein, we studied cryptic diversity of a high elevation clade from premontane and montane forest of Chiriquí Province (Panamá), Cordillera Oriental (Ecuador), and Valle del Silencio (Costa Rica). Additionally, we disentangle relationships of M. k. keaysi and M. k. pilosatibialis by determining their phylogenetic placement within the Neotropical Myotis radiation. In the process, we identified a new lineage of species level hierarchy that is described herein. We used an integrative taxonomy approach, using a combination of linear morphometrics, qualitative morphology, molecular phylogenetics, and climatic analysis. The newly identified lineage is a sister species to M. pilosatibialis str., but differs from M. sp. (Quintana Roo, México), M. keaysi str., and M. oxyotus gardneri in size and other quantitative morphological characters in addition to both nuclear and mitochondrial DNA sequence divergence. Based on our phylogenetic analysis of partial cytochrome b sequence, the polyphyly of M. keaysi str. and M. pilosatibialis str. is resolved, with M. keaysi str. paraphyletic to M. ruber and M. simus. Myotis pilosatibialis is part of a monophyletic clade that is sister to the newly identified species. This report refines our understanding of taxonomy and systematics of the Myotis pilosatibialis complex of bats, identifies and describes a new species of Myotis, and more broadly it contributes to efforts to characterize species in this genus in Neotropical environments. Based on its distribution, we classified this newly described species as paramontane due to its restriction to premontane and montane forest of Chiriquí Province (Panamá), Valle del Silencio (Costa Rica), and Cordillera Oriental (Ecuador). These habitats are susceptible to the effects of climate change, in addition to ongoing habitat destruction.